Diagnosis of poultry mycoplasmosis by cultural isolation and PCR - KAMBLE, S Y; GANDGE, R S; MAJEE, S B (The Indian Journal of Animal Sciences, 2015)
The present investigation was designed for diagnosis of poultry mycoplasmosis by cultural isolation and PCR assay. Clinical specimens (159: 47 lungs, 21 trachea, 91 choanal cleft swabs) of poultry were simultaneously subjected to cultural isolation of Mycoplasma spp., PCR for detection of mycoplasmosis and for isolation of E. coli. Isolation of Mycoplsma spp. was carried out using pleuropneumonia like organism (PPLO) medium. Identification of genus Mycoplasma and differentiation from Acholeplasma and Ureaplasma was done by conventional methods. A total of 15 isolates were identified as Mycoplasma spp. with isolation rate of 9.43%. In MG (Mycoplasma gallisepticum) and MS (Mycoplasma synoviae) species specific 16S rRNA PCR assay, all 15 isolates were confirmed as MG species. Direct detection of mycoplasmosis in 159 clinical specimens by PCR, targeting MG and MS species-specific 16S rRNA gene, revealed 108 (67.92%) positive specimens. Out of 108, 105 (66.04%) and 3 (1.86%) were positive for MG and MS respectively. E. coli was found to be major pathogen associated with poultry mycoplasmosis in 28 MG-PCR positive cases out of 42 E. coli isolates recovered. Comparative results of PCR and cultural isolation showed that 16S rRNA MG and MS species specific PCR is superior to cultural isolation for crucial, rapid, specific and sensitive detection of poultry mycoplasmosis directly in clinical specimens.